Analisis Minat Mahasiswa Dalam Memilih Program Studi PGPAUD Di Universitas Dehasen Bengkulu Angkatan 2024 Kelas Reguler - Aryanti, Sely; Haryono, Mimpira; Nurwita, Syisva (Early Childhood Research and Practice, 2025)
This research aims to analyze students' interest in choosing the Early Childhood Education Teacher Education Study Program (PGPAUD) at Universitas Dehasen Bengkulu, Class of 2024 Regular Class. The focus of this study is on the factors of attention, curiosity, motivation, and needs that influence students' decisions in selecting PGPAUD. The methodology used is a qualitative approach with in depth interviews of PGPAUD students. The results indicate that attention to early childhood education, curiosity about career prospects, motivation, and self-development needs significantly affect students' decisions to choose PGPAUD. Students interested in this field due to the program offers broad career opportunities and contributes to children's development. In conclusion, students' interest is influenced by these factors, and it is recommended that the university clarify information about career prospects and job opportunities, as well as strengthen the promotion of the PGPAUD study program to attract prospective students.